Understanding the obesity epidemic among north Indian medical students: Prevalence, risk factors, and health implications - Aman Dev Singh; Harseerat Grewal; Simmi Oberoi; Aafia Sachdeva; Rohit Batish (Journal of Family Medicine and Primary Care)
Background: Obesity among medical students is a significant public health issue with various contributing factors, including dietary habits, physical activity, and genetic predisposition. This study aims to assess obesity prevalence and its associated factors among North Indian medical undergraduates. Aim: To assess the prevalence of obesity and its relationship with various factors among medical undergraduates in North India. Materials and Methods: This cross-sectional study was conducted from September 15, 2024, to October 15, 2024, at a tertiary care institute. All students from the MBBS Batch 2023 participated via convenient sampling. Data were collected through a Google form covering sociodemographic, dietary and physical habits, and mental health. Analysis was performed using SPSS Trial version 26. Results: Out of 208 students, 6% were underweight, 66.8% were normal weight, 17.8% were overweight, and 5.8% were obese. Significant associations were found between BMI and gender (P = .003), breakfast eating (P = .012), and family history of obesity (P = .006). Conclusion: Obesity prevalence among medical students in North India is influenced by a complex interplay of sociodemographic, lifestyle, and genetic factors. Targeted programs are needed to address these specific predictors and support health management in medical students.